Level of knowledge and perceived barriers of mammography among female lecturers in Kulliyyah of Allied Health Sciences ( KAHS ), IIUM, Kuantan, Pahang - Burhanuddin, Fatin Amirah; Soo Foon, Moey (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2018)
Introduction: Breast cancer is the commonest disease amongst women throughout the world and the second leading cause of women’s death. Since 2014, it was reported that approximately 5000 women were diagnosed with breast cancer every year in Malaysia. Adoption of mammography screening amongst Malaysian women remains under-utilized because it depends on self-initiative of individuals. Amongst the perceived barriers are low knowledge, cost, embarrassment and pain which may then give a negative psychological aspect to health behavior actions. The study aims to determine the level of knowledge and perceived barriers pertaining to mammography amongst female lecturers in Kulliyah of Allied Health Sciences (KAHS), International Islamic University Malaysia (IIUM) Kuantan, Pahang. Methods: A survey was carried out on female lecturers aged 35 years and above in KAHS, IIUM Kuantan. A self-administered questionnaire which consists of three sections; demographic factors, knowledge about breast cancer and perceived barriers pertaining to mammography were distributed to 30 respondents. Data were analyzed using SPSS version 19.0. Results: The mean age of respondents was 39.9 years old (SD ± 5.15). Majority of respondents possessed good knowledge of breast cancer. The perceived barriers pertaining to mammography amongst respondents were pain and the procedure is expensive. Conclusions: This study found that most female lecturers in KAHS, IIUM Kuantan possessed good knowledge of breast cancer but have fair knowledge pertaining to breast lumps and the best time for breast screening. The perceived barriers amongst respondents were pain and cost of the procedure.